2019
DOI: 10.1016/j.cemconres.2019.105807
|View full text |Cite
|
Sign up to set email alerts
|

A physical approach towards controlling the microstructure of metakaolin-based geopolymer foams

Abstract: Geopolymer foams are promising sustainable lightweight materials combining insulation efficiency with interesting mechanical and fire resistance properties. Controlling their pore size remains challenging because intrinsic foam aging processes act before hardening. We highlight a physical approach to counteracting aging processes in fresh geopolymer foams and to maintaining the pore morphology that has been set initially by mixing metakaolin suspension with precursor aqueous foam. More precisely, it is shown t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(14 citation statements)
references
References 35 publications
0
14
0
Order By: Relevance
“…Therefore, samples with same amount of additional H 2 O (11 wt%, z = 11) using different types of surfactants were also investigated. Figures 2-4 Previous works [34][35][36] showed that the nature of the surfactant plays an important role in the fabrication of porous geopolymers by direct foaming. Indeed, different surfactants showed different foaming ability for the geopolymer slurry (see Figures 2-4 (a, a) (z = o) and Figures 2-4 (c, c) (z = 11)).…”
Section: Pore Microstructurementioning
confidence: 99%
“…Therefore, samples with same amount of additional H 2 O (11 wt%, z = 11) using different types of surfactants were also investigated. Figures 2-4 Previous works [34][35][36] showed that the nature of the surfactant plays an important role in the fabrication of porous geopolymers by direct foaming. Indeed, different surfactants showed different foaming ability for the geopolymer slurry (see Figures 2-4 (a, a) (z = o) and Figures 2-4 (c, c) (z = 11)).…”
Section: Pore Microstructurementioning
confidence: 99%
“…This material is also referred to as foam concrete, which by definition is a cellular concrete with a large number of hollow spaces, with or without the addition of aggregate [ 9 ]. They have good thermal insulation and acoustic properties [ 10 , 11 , 12 , 13 ] as well as mechanical properties, although their compressive strength is lower than that of solid (not foamed) geopolymers [ 10 , 14 ]. The comparison of fire-resistant properties of geopolymers and other materials is shown in Figure 1 [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, numerous works are still devoted to elucidate the link between their microstructure and their macroscopic properties, such as thermal, acoustical, mechanical, and transport properties (Despois and Mortensen, 2005;Doutres et al, 2011;Gibson and Ashby, 1997;Jang et al, 2008;Kumar and Topin, 2014). Recently, mineral solid foams, made from cement or geopolymer or gypsum, have been studied for their applications as building materials, requiring a good compromise between mechanical strength, and sound and/or thermal insulation (Chevillotte et al, 2013;Feneuil et al, 2019;Hung et al, 2014;Kaddami and Pitois, 2019;Zhang et al, 2014). This kind of solid foam differs from polymeric foams, which are widely used for sound and/or thermal insulation by both their wide range of porosity (from 0.65 to 0.95) and their highly stiff porous frames.…”
Section: Introductionmentioning
confidence: 99%
“…A millifluidic setup, described in detail in Kaddami and Pitois (2019), is used to generate monodisperse foam (Fig. 3).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation